Educational orders as a diversionary treatment model and their use in the practice of the Higher Public Prosecutor’s Office and the High Court in Novi Sad - Bugarski, Tatjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Juvenile crime is constantly attracting the attention of the general and professional public and in some way is an indicator of the success or failure of all measures by which a society takes care of the young. As a particularly vulnerable category, juveniles are the focus of special attention in each society which constantly invents always new and more efficient ways of solving criminal matters which will cause a minimum damage to a juvenile offender, and achieve the purpose that is reflected in the strengthening of its personal responsibility for its actions. In this sense, a special place occupies the application of educational orders that can achieve its purpose only if there is a complete legal regulation of their use (law and regulations) and systematically provided logistics. Imposition and implementation of educational orders is directly related to the examination of juvenile’s personality and a special attention has been paid to this issue. In this work, the author deals with educational orders as a diversionary treatment model against juvenile offenders, as well as the implementation of educational orders in the practice of the Higher Public Prosecutor’s Office and the High Court in Novi Sad.